Новый вид рода Hemidinium Stein (Dinophyta) из Израиля - Крахмальный, А.Ф.; Вассер, С.П.; Нево, Э. (Альгология, 2005)
Описан новый для науки вид Hemidinium nephroideum Krachmalny sp. nov. (Dinophyta), найденный в водоеме с дождевой водой в верхней части бассейна р. Орен в окрестностях г. Хайфы (Израиль). H. nephroideum имеет признаки родов Hemidinium Stein и Bernardinium Chodat, однако из-за структурированности теки авторы относят его к роду Hemidinium. В статье приводится диагноз нового вида, сравнение его с близким H. nasutum Stein, оригинальные рисунки и СЭМ фотографии. New species Hemidinium nephroideum Krachmalny sp. nov. (Dinophyta) was found in a rain pool in the upper section of Nahal Oren basin, Mount Carmel near Haifa (Israel). H. nephroideum has common features with representatives of genera Hemidinium Stein and Bernardinium Chodat. Due to the theca structure the authors refer the new species to the genus Hemidinium. In the paper we present diagnosis of new species, its comparison with a similar species, H. nasutum Stein, and original drawings and SEM - microphotographs.